2020
DOI: 10.1002/path.5534
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial to mesenchymal transition during neonatal hyperoxia‐induced pulmonary hypertension

Abstract: Bronchopulmonary dysplasia (BPD), a chronic lung disease in premature infants, results from mechanical ventilation and hyperoxia, amongst other factors. Although most BPD survivors can be weaned from supplemental oxygen, many show evidence of cardiovascular sequelae in adulthood, including pulmonary hypertension and pulmonary vascular remodeling. Endothelial-mesenchymal transition (EndoMT) plays an important role in mediating vascular remodeling in idiopathic pulmonary arterial hypertension. Whether hyperoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…We also reported that, in mice, hyperoxic exposure for 3 days as neonates causes pulmonary vascular remodeling, vessel obliteration, and pulmonary hypertension in adulthood (41). Ongoing studies will further determine whether neonatal hyperoxia chronically increases the PPP and EC proliferation, leading to vessel obliteration and subsequent pulmonary hypertension in adulthood.…”
Section: This Indicates That the Ppp And Glycolysis Differentially Comentioning
confidence: 69%
“…We also reported that, in mice, hyperoxic exposure for 3 days as neonates causes pulmonary vascular remodeling, vessel obliteration, and pulmonary hypertension in adulthood (41). Ongoing studies will further determine whether neonatal hyperoxia chronically increases the PPP and EC proliferation, leading to vessel obliteration and subsequent pulmonary hypertension in adulthood.…”
Section: This Indicates That the Ppp And Glycolysis Differentially Comentioning
confidence: 69%
“…Newborn C57BL/6J mice (<12 h old, male and female) along with their mothers were exposed to room air or hyperoxia (>95% O 2 ) for 72 h in an A-chamber (BioSpherix, Parish, NY) [ 29 , 30 ]. The dams were switched every 24 h between room air and hyperoxia to avoid injury.…”
Section: Methodsmentioning
confidence: 99%
“…The sex differences have been replicated in murine models and are strain specific ( 3 , 4 ). Male mice have greater alveolar simplification, impaired pulmonary vascular development, and more long-term adverse sequelae compared with female mice ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%